2019
DOI: 10.1182/bloodadvances.2019000200
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical vs haplo-cord transplant in adults under 60 years receiving fludarabine and melphalan conditioning

Abstract: Haplo-identical transplant with posttransplant cyclophosphamide (haplo) and umbilical cord blood transplant supported by third-party CD34 cells (haplo-cord) are competing approaches to alternative donor transplant. We compared, in adults younger than age 60 years, the outcomes of 170 haplo at 1 institution with that of 137 haplo-cord at 2 other institutions. All received reduced intensity conditioning with fludarabine and melphalan ± total body irradiation. GVHD prophylaxis for haplo consisted of cyclophospham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 28 publications
(70 reference statements)
3
14
0
Order By: Relevance
“…Multiple strategies are under investigation to improve the safety and efficacy of CBT. Ex vivo expansion of cord blood units [47][48][49] and co-infusion of haploidentical PBSC grafts with cord blood units [50] may allow faster engraftment and reduce the risk of graft failure with CBT. The single-center retrospective analysis by Milano et al showed that CBT may offer a better graft-versusleukemia (GVL) effect and lower the risk of relapse in patients with measurable residual disease (MRD) before transplantation compared to unrelated donor transplantation [51].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple strategies are under investigation to improve the safety and efficacy of CBT. Ex vivo expansion of cord blood units [47][48][49] and co-infusion of haploidentical PBSC grafts with cord blood units [50] may allow faster engraftment and reduce the risk of graft failure with CBT. The single-center retrospective analysis by Milano et al showed that CBT may offer a better graft-versusleukemia (GVL) effect and lower the risk of relapse in patients with measurable residual disease (MRD) before transplantation compared to unrelated donor transplantation [51].…”
Section: Discussionmentioning
confidence: 99%
“…Our result was consistent with Margaret's one that the incidence of grade II-IV acute GVHD in dUCBT recipients was higher than that in single UCBT recipients, but not grade III-IV aGVHD (31). Besien et al showed that cumulative incidence of grade II-IV acute GVHD was 16% after haplo-cord HSCT and 33% after haplo-HSCT (p <0.0001), but grade III-IV GVHD was similar (25). Kwon et al had similar results on treating AML.…”
Section: Discussionsupporting
confidence: 92%
“…The haploidentical graft serves as an early myeloid bridge for the recipient to support the immune system, which provides the rapid initial granulocyte and platelet recovery. This role of "myeloid bridge" was observed and confirmed for cord engraftment in patients receiving haplo-cord HSCT (25,26). There was a similar result in our study; myeloid engraftment occurred at a median of 14 days for patients with haplo-cord HSCT that was earlier than the median of 17 days in single cord HSCT recipients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The major limitation of using CBU is a relatively lower hematopoietic stem cell dose per unit for an adult recipient, leading to delayed engraftment and increased infectious complications and resultant NRM. Several strategies are under investigation to overcome this limitation to shorten the duration of neutropenia such as double-cord transplant [78], ex vivo expanded CBU [79], and coinfusion of a haploidentical RD graft with CBU (haplo-cord transplant) [80].…”
Section: Faq8: Is Auto-hct a Good Alternative To Consolidative Chemotherapy If Not Eligible For Allo-hct?mentioning
confidence: 99%